Biodegradation of Pesticides at the Limit: Kinetics and Microbial Substrate Use at Low Concentrations - Johannes Wirsching; Holger Pagel; Franziska Ditterich; Marie Uksa; Martina Werneburg; Christian Zwiener; Doreen Berner; Ellen Kandeler; Christian Poll (Frontiers in Microbiology, 2020)
The objective of our study was to test whether limited microbial degradation at low pesticide concentrations could explain the discrepancy between overall degradability demonstrated in laboratory tests and their actual persistence in the environment. Studies on pesticide degradation are often performed using unrealistically high application rates seldom found in natural environments. Nevertheless, biodegradation rates determined for higher pesticide doses cannot necessarily be extrapolated to lower concentrations. In this context, we wanted to (i) compare the kinetics of pesticide degradation at different concentrations in arable land and (ii) clarify whether there is a concentration threshold below which the expression of the functional genes involved in the degradation pathway is inhibited without further pesticide degradation taking place. We set up an incubation experiment for four weeks using 14C-ring labeled 2-methyl-4-chlorophenoxyacetic acid (MCPA) as a model compound in concentrations from 30 to 20,000 μg kg–1 soil. To quantify the abundance of putative microorganisms involved in MCPA degradation and their degradation activity, tfdA gene copy numbers (DNA) and transcripts (mRNA) were determined by quantitative real-time PCR. Mineralization dynamics of MCPA derived-C were analyzed by monitoring 14CO2 production and 14C assimilation by soil microorganisms. We identified two different concentration thresholds for growth and activity with respect to MCPA degradation using tfdA gene and mRNA transcript abundance as growth and activity indices, respectively. The tfdA gene expression started to increase between 1,000 and 5,000 μg MCPA kg–1 dry soil, but an actual increase in tfdA sequences could only be determined at a concentration of 20,000 μg. Accordingly, we observed a clear shift from catabolic to anabolic utilization of MCPA-derived C in the concentration range of 1,000 to 5,000 μg kg–1. Concentrations ≥1,000 μg kg–1 were mainly associated with delayed mineralization, while concentrations ≤1,000 μg kg–1 showed rapid absolute dissipation. The persistence of pesticides at low concentrations cannot, therefore, be explained by the absence of functional gene expression. Nevertheless, significant differences in the degradation kinetics of MCPA between low and high pesticide concentrations illustrate the need for studies investigating pesticide degradation at environmentally relevant concentrations.